Pesticide Safety Miniposter: Triple Rinse Steps - Rebecca W. Baldwin; Stephanie K. Larrick Hill; Philip Koehler; W. Walker; J. C. Medley (EDIS, 2012)
The Triple Rinse poster acquaints new pest management technicians to proper techniques to clean and dispose of empty pesticide containers. The poster uses quick response (QR) codes that direct smartphones to online videos that demonstrate the triple rinse process and container disposal. This poster will serve as a valuable training tool for new technicians and a refresher tool for pesticide applicators. Designed by R.W. Baldwin, S.K. Hill, Philip Koehler, W. Walker, and J.C. Medley, and published by the UF Department of Entomology and Nematology, August 2012.